Women taking out a procession carrying earthen pots - Mumbai Archive Project Team (Jio Institute, 2024)
Women take out a procession, carrying earthen pots on their heads. They circle the effigy five times before breaking the pots in the fire. This tradition traces back to a time when ceremonial fires were carried in earthen pots.